Análise eletromiográfica do m. rectus abdominis durante a retroversão pélvica e abaixamento dos membros inferiores - Martinelli, Rita de Cássia Pelizário Munhoz [UNIFESP] (2008)
We often face patients searching for rehabilitation for lower back disorders during the physiotherapeutic routine, and it is known that the abdominal muscle, specially the rectus abdominis muscle, aid the stabilization of the pelvis. Therefore, this paper analyzes the electrical activity of the rectus abdominis muscle in the pelvic retroversion in dorsal decubitus and in orthostatic position and in the lowering of the lower limbs. 30 healthy students, male and female, 17 – 40 yr, divided into two groups – Group 1: 15 volunteers (pelvic balance); Group 2 (pelvic unbalance) took part in this study. The electrical activity of the right and left supra-umbilical and infra-umbilical portions of the rectus abdominis muscle was detected. The mean RMS values from three attempts from the electromyographic traces were used for the analysis of the electrical activity. The RMS value was submitted to the normalization process. The data were submitted to statistic treatment by the Friedman test, and the analyses of the means and standard deviation towards a level of significance of 95%. The results demonstrated that the portions of the rectus abdominis muscle presented low electrical activity for the groups studied for pelvic retroversion either in dorsal decubitus or and orthostatic position. However, the decreasing movement of the lower limbs towards the portions of the rectus abdominis muscle presented more significant electrical activity whereas the lower portions presented higher activity than the higher ones for Group 2. 29